Abortion and elections: Brazil going against the current of Uruguay and Argentina - Matos, Maurílio Castro de; Santos, Franciele da Silva; Araújo, Tatianny de Souza de (Argumentum, 2023)
Abstract: The article draws a parallel between the realities of Argentina and Uruguay and that of Brazil regarding the decriminalisation and legalisation of abortion as a right of pregnant women and people, the discussion being in the context of electoral campaigns. In the former, legalisation was based on commitments by individual presidential candidates to sanction the law, after approval by their National Congresses. In Brazil, this reality does not exist, given the tense and polarised debate on the subject in the National Congress and the presence of a strong conservative wave in various sectors of the country. It focuses on bibliographic research and media data, with a qualitative approach. The different realities express a mismatch between Brazil and Argentina and Uruguay, because though they share similar realities, Brazil is far removed in terms of effecting legalisation of abortion.Keywords: Legalisation of abortion. Election campaigns. Women’s rights. Southern Cone.